Optimization of waste management in developing countries with spatial approaches (Study case: Depok City and Curitiba City). Issue 1 (August 2020) - Amri, S; Soesilo, T E B.; Martono, D N; Supriatna,
Abstract: Waste management is a challenge for city authorities in developing countries especially due to increase of waste. The burden that is incurred on the city budget as a result of the high costs associated with its management and lack of understanding of the diversity of factors that influence the various stages of management. Comparative and descriptive analysis are utilized in this paper to observe the differences that arise at various levels of the administration so that they can be analysed. Data are collected from journal publications starting in 2013-2019. This paper compares how the handling of waste management has used a spatial approach starting from the Asian, Indonesian, and Depok levels. The purpose of this research is to find out what areas of waste management can be solved by spatial approaches, and recommendations for solutions that can be applied to the Depok City based on success story in other countries or regions. The Depok City already has a community-based approach that runs the trash bank. However, the waste bank is still ineffective, despite the low level of waste collection in Depok City. The optimization of waste management in Depok City can be improved its accuracy using spatial approach.